Comparative analysis of the recent publication trends in 4 representative journals in the spine field. Issue 45 (12th November 2021) - Yang, Kuhyun; Baek, Hong-Gyu; Cho, Dae-Chul; Jung, Yoon Gyo; Lee, Subum; Park, Jin Hoon
Abstract : Abstract: We have analyzed and compared the publication trends in 4 representative spinal journals [ Spine, European Spinal Journal (EUS), The Spine Journal (TSJ), and the Journal of Neurosurgery – Spine (JNS spine) ] from 2016 to 2018. A total of 3784 articles were published in the 4 representative journals: 1358, 1128, 685, and 613 articles in Spine, EUS, TSJ, and JNS spine, respectively. We compared and analyzed each periodical for the time taken (days) for the publication process, the distribution of specialties of the corresponding author, multicity of the investigative institutions, main disease entity, study type, and design. The period from submission to online publication was 133, 216, 181, and 318 days in Spine, EUS, TSJ, and JNS spine, respectively. Corresponding authors with orthopedic specialties were more common in Spine, EUS, and TSJ than in JNS spine . Of particular note, corresponding authors who were neurosurgeons were the majority (55.8%) only in JNS spine. Single institution articles were by far the most common (average 92.8%) in all 4 journals. In all of the analyzed journals, the proportion of degenerative diseases was dominant with an average of 44.9%. The most frequent study type in all 4 journals was a clinical article (79.6, 72.1, 63.3, and 63.1%, respectively). In general, meta-analyses (average 4%) and randomized controlled comparative studies (average 5.2%) accounted for a very low percentage of the study types. We believe that periodic analyses and comparisons of the characteristics of representative spine journals will help to shape the direction of future improvements.